Social work intervention - Lindsay, Trevor; Jayat, Cathy; McGinnis, Emma (Thousand Oaks, CA : Sage Publications, 2017)
Since launching in 2003, Transforming Social Work Practice has become the market-leading series for social work students. These books use activities and case studies to build critical thinking and reflection skills and will help social work students to develop good practice through learning. Social workers need to have a sound working knowledge of intervention as they are often balancing complex and sometime stressful circumstances with the individual needs of the service users. Also, as there are a wide range of social work interventions in current practice, students will benefit from knowing the advantages and disadvantages of each model and approach. This book on effective social work intervention will help students apply and integrate this knowledge in practice, to critically evaluate different methods and to choose ...
Description based on MARC record for print version.
Keywords: Social service